Predominance of KPC-3 in a Survey for Carbapenemase-Producing Enterobacteriaceae in Portugal - Manageiro, Vera (2015)
Among the 2,105 Enterobacteriaceae tested in a survey done in Portugal, 165 were nonsusceptible to carbapenems, from which 35 (26 Klebsiella pneumoniae, 3 Escherichia coli, 2 Enterobacter aerogenes, and 3 Enterobacter cloacae isolates and 1 Klebsiella oxytoca isolate) were confirmed to be carbapenemase producers by the presence of 30 Tn4401d-blaKPC-3, 4 intI3-blaGES-5, and one intI1-blaVIM-2 gene, alone or in combination with other bla genes. The dissemination of blaKPC-3 gene carried by an IncF plasmid suggests lateral gene transfer as a major mechanism of dissemination.